2014
DOI: 10.1111/asj.12342
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fat content on sensory characteristics of marbled beef from Japanese Black steers

Abstract: To analyze the sensory characteristics of meat samples with a crude fat content between 23.8% and 48.6% taken from 34 Japanese Black steers, we grilled the meat and subjected it to analytical sensory evaluation. We also measured the amounts of moisture, protein, nucleic acid and glutamic acid. An increase in crude fat content increased the tenderness, juiciness, and fattiness in the meat quality evaluation. An increase in crude fat content reduced the crude protein and moisture contents; it also slightly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 28 publications
4
34
0
1
Order By: Relevance
“…For chemical composition, Iida et al . () demonstrated a strong relationship between BMS and CF content of meat. Regarding meat quality evaluation, Iida et al .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…For chemical composition, Iida et al . () demonstrated a strong relationship between BMS and CF content of meat. Regarding meat quality evaluation, Iida et al .…”
Section: Introductionmentioning
confidence: 84%
“…Regarding meat quality evaluation, Iida et al . () also reported that increased CF content reduced the crude protein (CP) and moisture content and increased tenderness, juiciness and fattiness. Regarding sugar, Glu and fructose (Fru) may contribute to the sweetness in meat (MacLeod ), and these water‐soluble compounds contribute to the formation of meat flavor upon heating through the Maillard reaction (Mottram ).…”
Section: Introductionmentioning
confidence: 93%
“…Water-soluble compounds are generally expressed in the form of content of meat (Feidt et al 1996;Cornet & Bousset 1999;Koutsidis et al 2008aKoutsidis et al , 2008b, but given that taste is based on dissolved water-soluble compounds reacting with the taste buds (Iida et al 2015), we elected to investigate the genetic effects of the concentrations of water-soluble compounds in both meat and moisture. Descriptive statistics of water-soluble compounds are shown in Table 2.…”
Section: Effect Of Aging Period Heritabilities and Genetic Correlatimentioning
confidence: 99%
“…Korean consumers prefer QG 1 ++ or 1 + beef because of its high IMF content (Kim et al , 1999). Iida et al (2015) have demonstrated that an increase in crude fat content (range 23.8-48.6%) can increase the tenderness, juiciness, and fattiness. However, they also reported that an increase in crude fat content can reduce the crude protein content and slightly reduce the content of umami components such as nucleic acid and glutamic acid.…”
Section: Marbling Of Wagyu and Hanwoo Beefmentioning
confidence: 99%